An intraoral approach to minimize morbidity in a pediatric trauma case - Baskara, Bima; Bernardo, Lucas Pedro; Rahajoe, Poerwati Soetji; Sejati, Bramasto Purbo; Haryosuwandito, Erdananda (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: Maxillofacial fractures are rare in children. The treatment of fractures in children differs from that of adults due to the growth process of the jaw and dental development. The intraoral approach does not result in facial scars or nerve injury. Furthermore, it allows direct visualization of occlusion confirmation during the plate placement. Purpose: This case report describes a pediatric comminuted mandibular fracture that underwent open reduction with an intraoral approach. Case: A 13-year-old boy with a mandibular fracture was referred by the neurosurgery department. Clinical examination found a hematoma in the left submental region and discontinuity of the mandibular symphysis without a wound in the extraoral region. Coleman's sign and a vertical step between teeth 41 and 31 and teeth 33 and 34 with anterior open bite were found intraorally. A CT scan disclosed more than two fracture lines that involved the mandibular symphysis and a basal triangle fracture. The patient was diagnosed with a symphysis mandibular comminuted fracture with open bite malocclusion. Case management: Open reduction and reconstruction plate placement with an intraoral approach was performed under general anesthesia. The patient had no complaints during the two-month evaluation, and the plate was planned for removal in the third month postoperatively. Conclusion: In this case, open reduction with an intraoral approach was able to restore bone architecture without functional or aesthetic complications. This may be because the patient could be treated like an adult, as he had almost reached skeletal maturity due to his age. However, periodic observation is necessary to evaluate jaw growth.